The relationship between emotional intelligence, locus of control, self-efficacy, sense of coherence and work adjustment - Du Plessis, Anita Gesiena (Stellenbosch : Stellenbosch University, 2014)
Thesis (MComm)--Stellenbosch University, 2014.